2023
DOI: 10.1097/aln.0000000000004746
|View full text |Cite
|
Sign up to set email alerts
|

Meaning and Management of Perioperative Oliguria

Roberta Teixeira Tallarico,
Ian E. McCoy,
Francois Dépret
et al.

Abstract: Perioperative oliguria is an alarm signal. The initial assessment includes closer patient monitoring, evaluation of volemic status, risk–benefit analysisof fluid challenge or furosemide stress test, and investigation of possible perioperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…Intraoperative oliguria occurring in isolation should not trigger fluid boluses since the predictive value for postoperative AKI appears low [65]. An institutional series of the Mayo Clinic revealed that a certain degree of postoperative hypotension in up to 10% of patients may persist for less than 20 h without negatively impacting AKI occurrence, which affected <3% [66].…”
Section: Fluid Management In the Perioperative Period: Which Indicatorsmentioning
confidence: 99%
“…Intraoperative oliguria occurring in isolation should not trigger fluid boluses since the predictive value for postoperative AKI appears low [65]. An institutional series of the Mayo Clinic revealed that a certain degree of postoperative hypotension in up to 10% of patients may persist for less than 20 h without negatively impacting AKI occurrence, which affected <3% [66].…”
Section: Fluid Management In the Perioperative Period: Which Indicatorsmentioning
confidence: 99%